Implementation Of Islamic Values On Corporate Employees - M. Fauzan Anggara Lubis; Rudi Junjungan Sirait; Muhammad Qorib (Proceeding International Seminar of Islamic Studies, 2019)
Human resources is one important factor for the survival of a company or institution, because with the management of human resources the performance process of a company or institution can run well so that it supports the achievement of the vision, mission and objectives of the company. Along with the times of rapid economic development has led to many companies that no longer pay attention to Islamic values in the daily activities of the company in order to achieve corporate goals. This research aims to find out and analyze how the implementation of Islamic values on daily life employee day. This study uses a qualitative approach to the type of case study research. Data collection techniques used were observation, interviews, and documentation. The results of this study show that in daily life every employee of the company has adopted Islamic values where every female employee who is Muslim is required to wear the hijab, besides that during prayer hours all employees go to the mosque provided by the company and the company make recitation routine every month.